PISCO GETTING IN A PACKED DISTILLATION COLUMN BATCH - Otiniano Cáceres, Manuel Eduardo (2013)
We present the results of experimental runs performed far obtaining pisco in batch distillation column packed stainless steel from fermented wine of grape Quebranta.